Dimensional Standards of Seima-Turbino Castings with Eyes - Yu. I. Mikhailov (СибСкрипт, 2024)
The article features the dimensions applied by ancient figure casters. It summarizes the findings of eye molding forms for spearheads and axe blades from the Ob-Irtysh interfluve. The initial reference point for marking the negative tip of the spearhead was the toe length, which determined the bushing length as 2 to 1. After removing the contours of the bushing, the master marked the maximum width of the toe on the negative of the casting mold. The conditional points were in the middle of the spearhead length. The central rib (stiffening rib) corresponded to the length of the toe, and the endings of the parallel lateral ribs (teeth) fell on the maximum expansion of the toe. The upper edge of the eye and the upper line of the belt were marked at a distance equal to the outer diameter of the bushing towards the blade. The reconstructed system of relations between the whole and its parts could be defined as the dimensional standard observed by the master. The hook under the toe gave it the necessary structural strength. It prevented the toe from sinking, and the fracture did not load along the line of connection between the toe and the bushing. The new dimensional standard occurred as the position of the fork in the spearhead design changed. The Seima-Turbino axes also had a 2 to 1 ratio. Initially, the edge of the eye was marked at a distance equal to half the length of the vent of the bushing. Then, the eye was designed in the vent direction. In Samus-Kizhirovo moldings, the eye was modeled not in the direction of the vent of the bushing, but in the opposite one, i.e., to the blade. The single-eye design was original, and the two-eye products appeared as a result of its modification that made it possible to spearheads and axes with solid eyes.